2018
DOI: 10.1200/po.18.00075
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Infiltrating Lymphocyte Function Predicts Response to Neoadjuvant Chemoradiotherapy in Locally Advanced Rectal Cancer

Abstract: Purpose The presence of tumor-infiltrating lymphocytes (TILs) in tumors is superior to conventional pathologic staging in predicting patient outcome. However, their presence does not define TIL functionality. Here we developed an assay that tests TIL cytotoxicity in patients with locally advanced rectal cancer before definitive treatment, identifying those who will obtain a pathologic complete response (pCR). We also used the assay to demonstrate the rescue of TIL function after checkpoint inhibition blockade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 41 publications
(54 reference statements)
1
48
0
Order By: Relevance
“…As one solution, immune checkpoint treatment has been performed on epithelial-only submerged Matrigel organoids reconstituted with exogenous immune components [ 72 , 73 ]. Notably, co-culture of patient derived-tumor-only organoids with autologous TILs after expansion of organoids and TILs separately, enabled TIL migration toward PDOs through Matrigel, and tumor cell cytotoxicity, suggesting the use of this co-culture system to assess cytotoxic TIL function [ 72 ].…”
Section: Applying Organoids To Cancer Immunotherapy Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…As one solution, immune checkpoint treatment has been performed on epithelial-only submerged Matrigel organoids reconstituted with exogenous immune components [ 72 , 73 ]. Notably, co-culture of patient derived-tumor-only organoids with autologous TILs after expansion of organoids and TILs separately, enabled TIL migration toward PDOs through Matrigel, and tumor cell cytotoxicity, suggesting the use of this co-culture system to assess cytotoxic TIL function [ 72 ].…”
Section: Applying Organoids To Cancer Immunotherapy Researchmentioning
confidence: 99%
“…As one solution, immune checkpoint treatment has been performed on epithelial-only submerged Matrigel organoids reconstituted with exogenous immune components [ 72 , 73 ]. Notably, co-culture of patient derived-tumor-only organoids with autologous TILs after expansion of organoids and TILs separately, enabled TIL migration toward PDOs through Matrigel, and tumor cell cytotoxicity, suggesting the use of this co-culture system to assess cytotoxic TIL function [ 72 ]. The potential application for immunotherapy screening was suggested by co-culture of patient-derived tumor spheroids with autologous TILs treated with immunomodulatory antibodies targeting MICA/B and NKG2A antigens in colorectal cancer (CRC) [ 73 ].…”
Section: Applying Organoids To Cancer Immunotherapy Researchmentioning
confidence: 99%
“…Importantly, co-cultures of expanded T cells with organoid generated from adjacent healthy epithelial tissue resulted in undisturbed organoid expansion without significant levels of organoid cytotoxicity [107]. In another approach, tumour-infiltrating T cells and CRC organoids were separately expanded using their respective gold standard methods and then combined to assess T cell-mediated organoid killing [111]. Interestingly, the extent of cell death in the in vitro co-culture assay correlated well with the patient's response to chemotherapy and immune checkpoint blockade [111].…”
Section: Immuno-oncology and The Tumour Microenvironment In A Dishmentioning
confidence: 99%
“…In another approach, tumour-infiltrating T cells and CRC organoids were separately expanded using their respective gold standard methods and then combined to assess T cell-mediated organoid killing [111]. Interestingly, the extent of cell death in the in vitro co-culture assay correlated well with the patient's response to chemotherapy and immune checkpoint blockade [111]. Furthermore, the authors tested immune checkpoint blockade using PD1 antibodies in their coculture model system and demonstrated that organoid killing by PD1 high T cells was improved upon antibody treatment.…”
Section: Immuno-oncology and The Tumour Microenvironment In A Dishmentioning
confidence: 99%
“…Organoids can be used to help predict and prognosticate patient responses to therapy. Early studies with rectal cancer have shown that organoids can help predict rectal cancer responses to chemoradiotherapy . This could potentially change how we treat rectal cancer in the future.…”
mentioning
confidence: 99%